KEMAMPUAN GURU DALAM MENERAPKAN PEMBELAJARAN TEMATIK DI SDN ALALAK TENGAH 1 - Rivada, Feby Suci Amanda; Marini, Fika; Hidayatullah, Muhammad; Mulyani, Sri; Yuniar, Tya; Aslamiah, Aslamiah; Pratiwi, Diani Ayu (Elementar : Jurnal Pendidikan Dasar, 2025)
Minister of National Education Regulation Number 41 of 2007 indicates the use of a thematic approach in learning grades 1 to 3 of elementary school (SD). Even today, after the implementation of the 2013 Curriculum, a thematic approach must be implemented from grade 1 to grade 6 in the learning process. It is important for elementary school teachers to be able to implement a thematic approach as a professional responsibility. This research aims to: 1) analyze elementary school teachers' understanding of the thematic approach, 2) obtain a profile of elementary school teachers' abilities in implementing the thematic approach, and 3) determine teachers' obstacles in implementing the thematic approach in elementary schools. The research used a qualitative descriptive method with research subjects being grade 1 to grade 3 teachers at SDN Alalak Tengah 1 Banjarmasin. Data was collected by observation and interviews. Triangulation was carried out via Google From between researchers, teachers and school principals. The research results show that conceptually teachers understand the thematic approach well, but in practice 4 out of 6 teachers studied did not implement the thematic approach in learning. This research also reveals that most teachers experience obstacles in implementing a thematic approach to the learning process.